PERBANDINGAN EFEKTIFITAS PEMBERIAN JERUK BALI (CITRUS GRANDIS)DAN JERUK LEMON (CITRUS LIMON) TERHADAP INTENSITAS MUAL DAN MUNTAH PADA IBU HAMIL DI PUSKESMAS LANGSA KOTA TAHUN 2019 - Cut Mutiah (JURNAL KESEHATAN INDRA HUSADA, 2020)
Morning Sickness is a problem that often occurs in pregnant women trimester I. The incidence of nausea is 27-30%, while vomiting as much as 28-52%. Nausea and vomiting that interfere with the activities and general conditions of pregnant women are called Hyperemesis Gravidarum. If not handled properly, it will cause symptoms of severe nausea and vomiting and persistent resulting in dehydration, electrolyte disturbances or nutrient deficiency.To find out Comparison of Effectiveness of Pomelo and Lemon on the Intensity of Nausea and Vomiting in Pregnant Women in Langsa City Health Centre.Quasi-experimental-posttest non equivalent control group design.The total sample in this study is the Total Population of 34 respondents.Data collection techniques in this study by observation using a checklist and RINVR questionnaire. Data analysis using the Paired sample t-test.The results of the Paired T-Test showed that both groups had an effect on significantly reducing the nausea of ​​vomiting in pregnant women with a p-value of 0,000 in Pomelo, and in the Lemon group p value of 0.029. However, judging by the average difference, Pomelo was better (4,118) compared to lemon (0.353).Pomelo is more effective in reducing the score of nausea and vomiting in pregnant women compared to lemon.